A systematic review on the prospects of X- and Y-sexed semen in ruminant livestock: implications for conservation, a South African perspective - Ngcobo, Jabulani Nkululeko; Nedambale, Tshimangadzo Lucky; Sithole, Sindisiwe Mbali; Mtileni, Bohani; Mpofu, Takalani Judas; Ramukhithi, Fhulufhelo Vincent; Chokoe, Tlou Caswel; Nephawe, Khathutshelo Agree (Frontiers in Veterinary Science, 2024)
South Africa is home to numerous indigenous and locally developed sheep (Nguni Pedi, Zulu, and Namaqua Afrikaner, Afrino, Africander, Bezuidenhout Africander, Damara, Dorper, Döhne Merino, Meat Master, South African Merino, South African Mutton Merino, Van Rooy, and Dorper), goat (SA veld, Tankwa, Imbuzi, Bantu, Boer, and Savanna) and cattle (Afrigus, Afrikaner, Bolowana, Bonsmara, Bovelder, Drakensberger, South African Angus, South African Dairy Swiss, South African Friesland, South African Red, and Veld Master) animals. These breeds require less veterinary service, feed, management efforts, provide income to rural and or poor owners. However, most of them are under extinction risks and some with unknown status hence, require immediate conservation intervention. To allow faster genetic progress on the endangered animals, it is important to generate productive animals while reducing wastages and this can be achieved through sex-sorted semen. Therefore, this systematic review is aimed to evaluate the prospects of X and Y-sexed semen in ruminant livestock and some solutions that can be used to address poor sex-sorted semen and its fertility. This review was incorporated through gathering and assessing relevant articles and through the data from the DAD-IS database. The keywords that were used to search articles online were pre-gender selection, indigenous ecotypes, fertility, flow cytometry, artificial insemination, conservation, and improving sexed semen. Following a careful review of all articles, PRISMA guidelines were used to find the articles that are suitable to address the aim of this review. Sex-sorted semen is a recently introduced technology gaining more attention from researchers particularly, in the conservation programs. Preselection of semen based on the sex chromosomes (X- and or Y-bearing chromosomes) is of paramount importance to obtain desired sex of the offspring and avoid animal wastage as much as possible. However, diverse factors can affect quality of semen of different animal species especially after sex-sorting. Flow cytometry is a common method used to select male and female sperm cells and discard dead and abnormal sperm cells during the process. Thus, sperm sexing is a good advanced reproductive technology (ART) however, it is associated with the production of oxidative stress (OS) and DNA fragmentation (SDF). These findings, therefore, necessitates more innovation studies to come up with a sexing technology that will protect sperm cell injuries during sorting in frozen-thawed.